Pengaruh Model GI-DMM Terhadap Hasil Belajar Sumatif Siswa Kelas XI Fase F : (The Effect of the GI-DMM Model on the Summative Learning Outcomes of Grade XI Phase F Students) - Insaniatul , Rahmi; Rosba, Evrialiani; Nerita, Siska (BIODIK, 2025)
This study was conducted in response to students’ low achievement in understanding the concept of the coordination system and the limited use of innovative, digital-based learning models. The purpose of this research is to investigate the effect of the Group Investigation learning model assisted by Digital Mind Mapping (GI-DMM) on students’ summative biology learning outcomes in Grade XI Phase F. This experimental research used a Randomized Control Group Posttest-Only Design. The population included all Phase F students of SMAN 5 Padang during the second semester of the 2024/2025 academic year. The sample consisted of two randomly selected classes: XI F4 (experimental group) and XI F7 (control group). The research instrument was a summative assessment in the form of multiple-choice questions. Data were analyzed using a t-test. The results showed that the experimental group had a higher average score (86.58) compared to the control group (73.41). The t-test result (t = 5.48 > t_table = 1.66) indicates a significant difference between the two groups. It is concluded that the GI-DMM learning model significantly improves students’ biology learning outcomes on the topic of the coordination system. Abstrak. Penelitian ini dilatar belakangi oleh rendahnya hasil belajar siswa dalam memahami konsep sistem koordinasi, serta kurangnya penggunaan model pembelajaran inovatif berbasis digital. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Group Investigation berbantuan Digital Mind Map (GI-DMM) terhadap hasil belajar sumatif biologi siswa kelas XI Fase F. Jenis penelitian ini adalah eksperimen dengan rancangan Randomized Control Group Posttest Only Design. Populasi penelitian adalah seluruh siswa Fase F SMA Negeri 5 Padang pada semester genap tahun pelajaran 2024/2025. Sampel terdiri dari dua kelas, yaitu XI F4 sebagai kelas eksperimen dan XI F7 sebagai kelas kontrol, yang dipilih menggunakan teknik simple random sampling. Instrumen penelitian berupa asesmen sumatif dalam bentuk soal pilihan ganda. Data dianalisis menggunakan uji-t. Hasil penelitian menunjukkan bahwa nilai rata-rata penilaian sumatif adalah 86,58 untuk kelas eksperimen dan 73,41 untuk kelas kontrol. Hasil uji-t menunjukkan bahwa t hitung sebesar 5,48 > t tabel 1,66, sehingga H1 diterima. Dengan demikian, model pembelajaran GI-DMM berpengaruh terhadap hasil belajar biologi siswa pada materi sistem koordinasi